Reshaping Toronto's waterfront - Desfor, Gene; Laidley, Jennefer, 1969- (University of Toronto Press, 2011)
"Large-scale development is once again putting Toronto's waterfront at the leading edge of change. As in other cities around the world, policymakers, planners, and developers are envisioning the waterfront as a space of promise and a prime location for massive investments. Currently, the waterfront is being marketed as a crucial territorial wedge for economic ascendancy in globally competitive urban areas.